Implementation Of Abraham Maslow’s Humanism Learning Theory In Overcoming Learning Disabilities In Islamic Religious Education - Azizah, Nurul; Ningsih, Nur Wahyu; Polem, Muhammad; Tarsono, Tarsono; Ruswandi, Uus (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
This study aims to analyze Abraham Maslow's humanism learning theory and how it is implemented in overcoming learning disabilities in Islamic religious education. This study used a qualitative research method with a library research approach. Data sources include books, journal articles, theses, and other information related to implementing Abraham Maslow's humanism learning theory in overcoming learning difficulties in Islamic religious education learning. The results showed that Maslow's theory of humanism offers a hierarchy of needs, which has five kinds of higher-level human needs, assuming that higher needs will be fulfilled if lower needs are met. According to Abraham Maslow, five kinds of the hierarchy of needs are physiological needs, safety needs, affection needs, esteem needs, and self-actualization needs. In overcoming learning difficulties in learning Islamic religious education, the implementation of the theory of the hierarchy of needs can be explained as follows; 1) Fulfillment of physiological needs is to ensure that the basic needs of students are met, 2) fulfillment of the need for security is not to show threatening behavior, criticize, or even judge students for their mistakes without knowing the cause, 3) fulfillment of the need for affection by showing empathy, caring, patience, fairness, and openness towards students, 4) fulfilling the need for self-esteem by giving freedom to students to express opinions and respecting students' own choices, 5) fulfilling the need for self-actualization by supporting and facilitating students in developing their potential by giving freedom to students to hone their potential abilities.   Keywords: Abraham Maslow, Humanism Learning theory, Learning Disabilities, The hierarchy of needs